Pengaruh Metode KWL (Know Want to Learn) terhadap Keterampilan dan Minat Membaca Siswa - Yudi Budianti; Novita Damayanti (Universitas Pendidikan Indonesia (UPI), 2017)
This research was conducted based on the low of the students’ skill and reading interest in Indonesian Subject in the fifth grade students of Madrasah Ibtidaiyah (MI) At Taubah Bekasi. This research was purposed to know the influence of the usage of Know Want To Learn (KWL) methode to the skill and reading interest of the short story in the fifth grade of Madrasah Ibtidaiyah At Taubah Bekasi in the educational year 2016/2017.The research methode used was experimental research methode using quasi experimental design with nonequivalent group design. The subject of this research was the students of VA class as an experimental class as many 25 students and class VB as a control class as many 25 students.The research result of the Reading Skill based on the result of the hypothesis test in experimental class was 9,307 and in the control class was 8,106 with dk 24 significant level α = 0,05. It was gained ttable 1,710 tcount ttable (9,307 1,710) thus Ho was rejected dan H1 was accepted. Meanwhile, the reading interest based on the result of the hypothesis test in experimental class was 6,221 and in the control class was 4,083 with dk 24 significant level α = 0,05. It was gained ttable 1,710 tcount ttable (6,221 1,710) thus Ho was rejected dan H1 was accepted. Thus, Know Want To Learn (KWL) methode had a positive influenced to the students’ skill and reading interest.